Amino Acid Uptake, Glucose Metabolism, and Neuroinflammation in John Cunningham Virus Associated Progressive Multifocal Leukoencephalopathy. (21st February 2022) - Unterrainer, Marcus; Mahler, Christoph; Schumacher, Adrian-Minh; Ruf, Viktoria; Blum, Bernhard; Quach, Stefanie; Brendel, Matthias; Rupprecht, Rainer; Bartenstein, Peter; Kerschensteiner, Martin; Kümpfel, Tania; Albert, Nathalie L.
Abstract: A 69-year-old woman presented with progressive dysarthria and cognitive deficits. On MRI, a T2-hyperintense, non–contrast-enhancing lesion was found in the left precentral area. 18 F-FET and 18 F-FDG PET scans revealed faint amino acid uptake and glucose hypometabolism of the lesion. To assess a neuroinflammatory component, TSPO PET with 18 F-GE-180 was performed, where tracer uptake markedly exceeded the T2-hyperintense areas. Histology derived from a stereotactic biopsy findings confirmed John Cunningham virus–associated progressive multifocal leukoencephalopathy. This case underlines that TSPO PET comprises distinct imaging advantages over other established radioligands such as 18 F-FET and 18 F-FDG in progressive multifocal leukoencephalopathy.